Youth-Oriented Digital Media Visibility on Instagram: A Multimodal Qualitative Analysis of USSFeeds - Muhammad Rajwa Ridho; Iman Sumarlan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Social media platforms have reshaped how visibility is produced, sustained, and contested within contemporary digital media environments. Despite extensive research on social media branding and engagement, limited attention has been given to how youth-oriented digital media actors strategically construct visibility as an ongoing communicative process rather than mere exposure. This study aims to examine how a youth-oriented digital media account builds and maintains visibility on Instagram through everyday visual, narrative, and participatory practices. Employing a qualitative content analysis, this research analyzes selected Instagram posts published by USSFeeds between March and September 2025. The analysis focuses on three analytical dimensions: visual discourse, narrative framing, and participatory circulation. The findings indicate that visual coherence operates as a semiotic anchor that stabilizes media identity, while narrative framing grounded in youth culture enhances cultural resonance and interpretive alignment. The audience participation amplifies visibility by enabling relational circulation of meaning within platform-mediated and algorithmically structured environments. This study contributes to media and communication scholarship by conceptualizing digital visibility as a relational and processual phenomenon shaped by discourse, participation, and platform logics, thereby extending existing understandings beyond linear models of attention and reach.